Do attitudes towards immigrants matter? - Gisela Waisman; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2007)
We exploit the regional variation in negative attitudes towards immigrants to Sweden in order to analyse what are the consequences of such attitudes have on immigrants welfare. A well educated immigrant from a non developed country who lives in a municipality with strong negative attitudes earns less than what she would earn if she lived in a municipality where natives are more positive. If attitudes changed from the average level to the most positive level, her wage would increase by 12%. This would reduce the wage gap to well-educated immigrants from developed countries by 70%. We interpret this eect as evidence of labour market discrimination. The same reduction in negative attitudes would increase the welfare of immigrants from Africa and Asia, through their wage and local amenities, by an equivalent to one third of their wage. The analogous amount for immigrants from South America and Eastern Europe is one fourth of their wage if they are well educated and one tenth otherwise.
hdl:10398/7587
Keywords: G10; 330